2010
DOI: 10.1021/nl1018194
|View full text |Cite
|
Sign up to set email alerts
|

Efficient, Ordered Bulk Heterojunction Nanocrystalline Solar Cells by Annealing of Ultrathin Squaraine Thin Films

Abstract: Spin-cast 2,4-bis[4-(N,N-diisobutylamino)-2,6-dihydroxyphenyl]squaraine (SQ) thin films only 62 A thick are converted from amorphous to polycrystalline via postannealing at elevated temperatures. The surface roughness of the SQ films increases by a factor of 2, while selected area electron diffraction spectra indicate an increase in the extent of postannealed film crystallinity. Dichloromethane solvent annealing is also demonstrated to increase the exciton diffusion length of SQ by a factor of 3 over thermally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
113
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 134 publications
(116 citation statements)
references
References 19 publications
2
113
0
1
Order By: Relevance
“…21 On the other hand, the cell using smooth ZnPc prepared 25 o C exhibits the almost highest IPCE in ZnPc absorption area.…”
Section: Resultsmentioning
confidence: 97%
“…21 On the other hand, the cell using smooth ZnPc prepared 25 o C exhibits the almost highest IPCE in ZnPc absorption area.…”
Section: Resultsmentioning
confidence: 97%
“…[4][5][6] A good performance of BHJ SMOSCs is only guaranteed if an interpenetrating network of the oligomeric donor (D) and an electron-acceptor (A), typically a fullerene derivative, is formed at the nanoscale as the photoactive layer. [7][8][9] Moreover, the size of the D and A homophases is crucially important for the diffusion of excitons to the D-A interface and after charge separation for effective charge transport to the electrodes. [2,[9][10][11] Investigation of the morphology of the phase-separated blend layers by transmission electron microscopy (TEM) [12] or X-ray diffraction (XRD) [13] have shed light into this complex puzzle.…”
Section: Doi: 101002/adma201104439mentioning
confidence: 99%
“…[7][8][9] Moreover, the size of the D and A homophases is crucially important for the diffusion of excitons to the D-A interface and after charge separation for effective charge transport to the electrodes. [2,[9][10][11] Investigation of the morphology of the phase-separated blend layers by transmission electron microscopy (TEM) [12] or X-ray diffraction (XRD) [13] have shed light into this complex puzzle. The use of small molecules in OSCs provides in contrast to polymeric materials another advantage: single crystals suitable for X-ray structure analysis become available providing detailed insight into intermolecular interactions and non-bonding atomic contacts responsible for the observed packing motifs.…”
Section: Doi: 101002/adma201104439mentioning
confidence: 99%
“…After a 30 min exposure to DCM, a second peak corresponding to the (002) refl ection appears, indicating a continued increase in order. [ 9 ] The mean crystal sizes of SQ in the blends annealed for 12 min and 30 min are estimated to be 2.0 ± 0.2 nm and 51 ± 4 nm, respectively, inferred from the XRD peak broadening using the Scherrer method. [ 15 ] The root-mean-square roughness obtained from the atomic force microscopy (AFM) images ( Figure 2 a) of the as-cast fi lm is 0.8 ± 0.1 nm.…”
mentioning
confidence: 98%
“…In past work, we have shown that solution-processed squaraine (SQ), followed by vacuum thermally evaporated C 60 donor/acceptor solar cells can have power conversion effi ciencies of η p = 4.6 ± 0.1% when they are fabricated into a lamellar device that is subsequently annealed at high temperature (110 ° C). [ 9 ] It was found that the annealing roughens the SQ surface, thereby creating a highly folded BHJ interface with the C 60 and thus compensating for the very short (1.Although the L D of SQ is very small, this defi ciency is partially compensated by its high absorption coeffi cient compared to that of C 60 . This motivates the use of SQ:fullerene blends, whereby the ratio of materials strongly favors that of the fullerene to take advantage of its large L D and low absorption.…”
mentioning
confidence: 99%